Role of Governance in Trade openness and FDI in various regional group countries: Africa Eastern and Southern, Africa Western and Central, North Africa - Sofian BOUHLEL (Košická bezpečnostná revue, 2023)
This paper investigates the critical role of governance in shaping trade openness and Foreign Direct Investment (FDI) inflows in three distinct regional groups within Africa: Eastern and Southern Africa, Western and Central Africa, and North Africa. Using several tests as OLS regression and granger causality, The study employs a comprehensive analysis of governance indicators, trade openness measures, and FDI data to discern the impact of governance on economic integration and investment attractiveness across these regions. The findings reveal significant variations in governance quality and its influence on trade and FDI within and among these regional groups. The research underscores the importance of good governance as a fundamental driver of economic development and integration in the African context.